An investigation on the effects of financial management skills, wealth and financial intelligence on investors’ risk tolerance: Empirical evidence from Tehran Stock Exchange - Saied Aghasi; Mohammad Reza Dalvi; Sahar Biglari (Management Science Letters)
During the past few years, Tehran Stock Exchange (TSE) has been changed into one of the most popular places to invest and index has been quadrupled in fewer than three years. As a result, many people have been attracted to invest on TSE market. This paper presents an empirical investigation to study the effects of investors’ personal characteristics including financial management skills, wealth and financial intelligence on investors’ risk tolerance among 384 randomly chosen investors who were active on TSE market in city of Esfahan, Iran. Using structural equation modeling, the study has determined that financial management skills, wealth and financial intelligence influence positively on investors’ risk tolerance.